Analytical High-resolution Electron Microscopy Reveals Organ-specific Nanoceria Bioprocessing. (January 2018) - Graham, Uschi M.; Yokel, Robert A.; Dozier, Alan K.; Drummy, Lawrence; Mahalingam, Krishnamurthy; Tseng, Michael T.; Birch, Eileen; Fernback, Joseph
This is the first utilization of advanced analytical electron microscopy methods, including high-resolution transmission electron microscopy, high-angle annular dark field scanning transmission electron microscopy, electron energy loss spectroscopy, and energy-dispersive X-ray spectroscopy mapping to characterize the organ-specific bioprocessing of a relatively inert nanomaterial (nanoceria). Liver and spleen samples from rats given a single intravenous infusion of nanoceria were obtained after prolonged (90 days) in vivo exposure. These advanced analytical electron microscopy methods were applied to elucidate the organ-specific cellular and subcellular fate of nanoceria after its uptake. Nanoceria is bioprocessed differently in the spleen than in the liver.